1992
DOI: 10.1093/cvr/26.8.783
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic and neurohumoral response in heart failure produced by rapid ventricular pacing

Abstract: These findings are compatible with a major role of one or more of renin, vasopressin, and noradrenaline in the pathophysiology of the fluid retention of heart failure; the manifestations are not counteracted by the rise in atrial natriuretic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 0 publications
3
20
0
Order By: Relevance
“…4,5 Furthermore, Weinberg et al 41 demonstrated that chronic administration of amlodipine normalized LV end-diastolic pressure in a model of LV hypertrophy. Consistent with past reports, [25][26][27][28][29][30][31][32] chronic rapid pacing caused LV dilation and pump dysfunction. In the present study, concomitant amlodipine monotherapy, ACE inhibition, or combination therapy instituted during chronic rapid pacing reduced the degree of LV dilation.…”
Section: Function and Systemic Hemodynamicssupporting
confidence: 91%
See 1 more Smart Citation
“…4,5 Furthermore, Weinberg et al 41 demonstrated that chronic administration of amlodipine normalized LV end-diastolic pressure in a model of LV hypertrophy. Consistent with past reports, [25][26][27][28][29][30][31][32] chronic rapid pacing caused LV dilation and pump dysfunction. In the present study, concomitant amlodipine monotherapy, ACE inhibition, or combination therapy instituted during chronic rapid pacing reduced the degree of LV dilation.…”
Section: Function and Systemic Hemodynamicssupporting
confidence: 91%
“…[25][26][27][28][29][30][31][32] Specifically, the development of pacing-induced CHF is associated with severe LV pump failure, heightened catecholamine levels, and increased vascular resistance in several circulatory beds. [25][26][27][28][29][30][31][32] In addition, the pacing model of CHF has been successfully used to examine specific systemic and neurohormonal changes that occur during exercise with the development of CHF. 27,29 Accordingly, in the present study, we used a pacing-induced model of CHF to examine the potentially differential effects of amlodipine treatment, ACE inhibition, and combined treatment on LV pump function, systemic hemodynamics, and regional blood flow patterns both at rest and with treadmill-induced exercise.…”
Section: Rationalementioning
confidence: 99%
“…First, we studied an animal model of RV pacing-induced HF that reproduces many of the functional and neurohormonal features (5,7,8,29,33,54) of clinical HF. Although this experimental model demonstrated biventricular chamber dilatation with increased LV and RV filling pressures and striking abnormalities in systolic and diastolic function similar to those found in patients with dilated cardiomyopathy, we cannot be certain that our results apply to HF of other causes such as hypertrophic cardiomyopathy.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Because the development of tachycardia-induced HF is reversible and the termination of rapid ventricular pacing results in improved cardiac and hormonal functions, 30 we performed these experiments with ongoing rapid ventricular pacing even though it is very important to assess the effects of the antagonist on changes in heart rate.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…30 However, even shorter-term pacing induces hemodynamic deterioration and some neurohormonal activation. Although it is important to assess exercise capacity, which is reduced in HF, to ascertain whether HF has been induced in this model, we could not assess it in the present study.…”
Section: Limitations Of the Studymentioning
confidence: 99%